Green Port Development — What Role Do Ports Play in Achieving Climate Goals? - Dörte Nitt-Drießelmann; Jan Wedemeier (Wirtschaftsdienst)
Abstract Maritime activities are an important part of the European economy as many goods are transported by ship. Ports are important players in the maritime sector because they provide the infrastructure for many maritime activities. Therefore, the potential impact of the port on the local carbon footprint should not be underestimated.